2017
DOI: 10.1016/j.neubiorev.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

How does mindfulness modulate self-regulation in pre-adolescent children? An integrative neurocognitive review

Abstract: Pre-adolescence is a key developmental period in which complex intrinsic volitional methods of self-regulation are acquired as a result of rapid maturation within the brain networks underlying the self-regulatory processes of attention control and emotion regulation. Fostering adaptive self-regulation skills during this stage of development has strong implications for physical health, emotional and socio-economic outcomes during adulthood. There is a growing interest in mindfulness-based programmes for pre-ado… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 281 publications
3
89
0
1
Order By: Relevance
“…It has been reported that P3b amplitude is sensitive to task difficulty (Polich, 2009), mindfulness training may increase attention flexibility and adjust attention resource allocation depending on task demands (Kaunhoven & Dorjee, 2017).The task accuracy rate in our study was very high, with all participants showing almost maximum accuracy (mean of 99 correct responses of a total of 100 targets, pre-post in both conditions). It is possible that the easy nature (based on our participant's skills) of our oddball task was insufficient to cause significant changes in the process underlying the P3b or uncover any modulation caused by mindfulness attitudes.…”
Section: Discussionsupporting
confidence: 43%
“…It has been reported that P3b amplitude is sensitive to task difficulty (Polich, 2009), mindfulness training may increase attention flexibility and adjust attention resource allocation depending on task demands (Kaunhoven & Dorjee, 2017).The task accuracy rate in our study was very high, with all participants showing almost maximum accuracy (mean of 99 correct responses of a total of 100 targets, pre-post in both conditions). It is possible that the easy nature (based on our participant's skills) of our oddball task was insufficient to cause significant changes in the process underlying the P3b or uncover any modulation caused by mindfulness attitudes.…”
Section: Discussionsupporting
confidence: 43%
“…Firstly, ML estimators require us to make a number of simplifying assumptions (see Discussion). These assumptions may be acceptable in well-trained, relatively homogeneous groups of adults, but may be inappropriate for children, who, for example, often exhibit high levels of inattentiveness (Godwin et al, 2016;Jones, 2018b;Jones, Kalwarowsky, Braddick, Atkinson, & Nardini, 2015;Kaunhoven & Dorjee, 2017;Manning, Jones, Dekker, & Pellicano, 2018;Moore, Ferguson, Halliday, & Riley, 2008;Smallwood, Fishman, & Schooler, 2007;Wightman & Allen, 1992;Witton, Talcott, & Henning, 2017), response bias (Trehub, Schneider, Thorpe, & Judge, 1991;Werner, Marean, Halpin, Spetner, & Gillenwater, 1992), and other nonstationary behaviors. The concern is that such deviations from an ''ideal'' observer might at best degrade the efficiency of the test compared to standard Staircases, and at worse may cause the results to become excessively noisy or biased.…”
Section: Introductionmentioning
confidence: 99%
“…Religious practices in the Buddhist frame can potentially lead to a self-regulatory mechanism that guides ones to act and behave prudently and in prosocial manner. Mindfulness meditation as part of the Buddhist practices has gained worldwide attention for its array of applications from cognitive behavioral therapy (Klingbeil et al, 2017) to enhancement of neurocognitive processes fundamental to self-regulation (Kaunhoven & Dorjee, 2017).…”
Section: Buddhism and Self-regulationmentioning
confidence: 99%